Characteristics and health risk assessment of heavy metals in indoor air of waterpipe cafés. (March 2021) - Rostami, Roohollah; Kalan, Mohammad Ebrahimi; Ghaffari, Hamid Reza; Saranjam, Behzad; Ward, Kenneth D.; Ghobadi, Hassan; Poureshgh, Yusef; Fazlzadeh, Mehdi
Abstract: This research characterized the concentrations of heavy metals in indoor air of waterpipe (WP) cafés. Fifty of the 236 WP cafés in Ardabil city, Iran were randomly selected and air samples were taken from standing breathing zones of smokers and staff ~150 cm above ground level. Concentrations of Ag, Al, As, B, Ba, Cd, Co, Cr, Cu, Fe, Hg, Mn, Mo, Ni, Sn, Sr, V, and Zn were determined in the samples using inductively coupled plasma optical emission spectrometry system (ICP-OES). Mean concentrations of the selected metals and their maximum values did not exceed workplace limit levels. However, concentrations were drastically higher than indoor air guidelines. For smokers, the average inhalation lifetime cancer risks (LTCRs) for As, Cd, Cr, and Ni were calculated 1.75 × 10 −5, 3.8 × 10 −6, 4.19 × 10 −4, and 7.79 × 10 −5, respectively. Also for employees, the mean LTCR of As, Cd, Cr, and Ni is 1.65 × 10 −4, 6.94 × 10 −5, 4.47 × 10 −3, and 8.17 × 10 −4, respectively. Except than the LTCR of Cd for the smokers, it was higher than the standard limit set by the US Environmental Protection Agency (EPA) and world health organization (WHO) for the remain metals. The mean of Hazard quotients (HQ) for Cr, Hg, and Mn were calculated to be 3.82, 0.02, and 0.73, respectively. WP smoking was the main source of the metals in indoor air of WP cafés and concentrations were especially high in cafés located in basements (vs. ground level) and which relied exclusively on natural ventilation. Graphical abstract: Image 1 Highlights: Waterpipe (WP) tobacco smoke is the main source of metals in the indoor air of WP cafés. Fruit flavored WP tobacco is much heavy metal emission source than the regular tobacco. Exposure to the WP smoke increase expected cancer risk due to the metal concentration. The mean of HQ for Cr were >1, indicating an unacceptably high-risk value.